Rumpictuside A: Unusual 9, 10-anthraquinone glucoside from Rumex pictus Forssk. (7th August 2017) - El-Kashak, Walaa A.; Elshamy, Abdelsamed I.; Mohamed, Tarik A.; El Gendy, Abd El-Nasser G.; Saleh, Ibrahim A.; Umeyama, Akemi
Abstract: A new 8-ionized hydroxylated 9, 10-anthraquinone namely, 1-hydroxy-3-methyl-9, 10-anthraquinone-6- O - β - D -glucopyranoside-8-olate (Rumpictuside A, 1 ) along with five known flavonoids, apigenin 7-O- β - D -glucoside (2 ), vitexin (3 ), quercetin 3- O - β - D -glucouronide (4 ), orientin (5 ), and isorientin (6 ) were isolated from Rumex pictus . The structures of isolated compounds were identified by the extensive spectroscopic techniques such as, UV, FT-IR, 1D, 2D NMR and HR-FAB-ESI-MS. The ionized hydroxyl group in the new anthraquinone (1 ) was rarely found for anthraquinone glycosides isolated from natural sources. All the isolated compounds were found inactive against influenza A virus infection. Compounds2–6 exhibited significant antioxidant activity against DPPH and ABTS + . The alcoholic extract exhibited moderate activity while the new anthraquinone1 showed the lowest activity against both assays. Graphical abstract: Highlights: Isolation of a new unusual 9, 10-anthraquinone. Isolation of five flavonoid glycosides for the first time from Rumex pictus Forssk. Screening of the isolated compounds against influenza A virus infection. Evaluation of the antioxidant activity in trolox equivalent of the alcoholic extract and the isolated compounds using DPPH and ABTS + assays.